Gender asymmetries: An exploratory study of women’s experiences in Portuguese football organizations - Santos, M. H.; Marques, A. M.; Salvador, J. (European Journal of Investigation in Health, Psychology and Education, 2024)
The main objective of this exploratory study is to analyze the negative effects associated with the phenomenon of tokenism for Portuguese women in non-playing football roles, as well as their strategies for integration into a context where they are a minority and the social functions are dominated by men. To this end, we carried out semi-structured individual interviews with eight men and eight women, undertaking functions in the fields of coaching, psychology, medical team, planning, refereeing, and management in football organizations, and with their contents then subject to thematic analysis. Our analysis confirms how the football context strongly demarcates gender differences with women being more visible and leads to the stereotypical roles being associated with traditional femininity. The findings also observe how, in order to integrate, women align with the norms imposed by the dominant group (men) and accept being circumscribed to the spaces that hegemonic gender ideologies and practices attribute to them.